INDIRECT METHODOLOGIES FOR MEASURING SOIL ERODIBILITY AND CHARACTERIZING ITS SPATIAL VARIABILITY - Lima, César Gustavo da Rocha; Bacani, Vitor Matheus; Montanari, Rafael; Vick, Erivelton Pereira; Ferreira, César Cardoso; Silva, Edson Rodrigo dos Santos da (Mercator, 2021)
The present study analyzed different indirect methodologies for measuring soil erodibility and characterized the spatial variability of soil erodibility in the Pântano River Hydrographic Basin (PRHB), state of Mato Grosso do Sul, Brazil. Nine methodologies/adaptations were tested in 103 soil samples collected covering the main soil types in the hydrographic basin. The data were submitted to a validation proposal and underwent descriptive and correlation statistical analyses. A spatial dependence analysis and mapping by kriging was also carried out. The methodologies that best represented the erodibility estimates at PRHB were those by Sharpley and Williams (Latossolos Vermelho-Escuros [Oxisols] and Planossolos [Alfisols]), Wischmeier and Smith (Latossolos Roxos [Oxisols]), and Renard (Podzólicos Vermelho-Escuros and Podzólicos Vermelho-Amarelos [Ultisols]). The final map indicated erodibility medium (46.4% of PRHB), low (45.1%), very low (0.5%) and very high (7.9%). The findings indicated that the use of a single indirect methodology may underestimate or overestimate the soil erodibility. Keywords : Pântano River Hydrographic Basin, Soil erosion, Kriging, Soil management and conservation, Mato Grosso do Sul.